Positioning of Participants’ Mood on Watches’ Advertising as Multimodal Discourse - Harmayanthi, Vera Yulia; Hardjanto, Njaju Jenny Malik Tomi (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Advertising is an activity to advertise products or services as central creation into the wider meaning of their messages. Its messages have to be applied which refer to readers’ needs and interests in the current trends. Creating appropriated messages in multimodal discourse is a form of technological advances in advertising, such as the existence of multimodal discourse in newspapers. That print media still has a special place for its readers which consider some advantages in building messages. Producers produce some messages at multimodal discourse through newspapers that are used as one of media promotions. This makes producers have to provide extra funds for the promotions’ activities. It of course needs to create the messages of products or services in strategically position. Especially, it is during a pandemic situation to a new normal era where everything has to be done completely. Messages should be able to reach wide readers as their prospected customers. The position of message in multimodal discourse should be placed appropriately to build an active interaction with their prospected customers. It could be seen on watches’ advertising in newspapers. This research used data of 3 watches’ advertisings on Kompas as one of the popular daily newspapers in Indonesia. They were published in 2017 and 2018 where products are intended specifically for male and female consumers. Analyzing this research applied qualitative method through systemic functional of Halliday’s theories to show interpersonal view between participants. The results of this research appeared the positioning of participants’ mood as a description of the interpersonal situations in their roles. Participants’ positioning defined their activations in building interaction on multimodal discourse that be purposed for male and female as their prospected consumers.